The Setbacks and Dilemmas of Medical Missionary Work: The Medical Endeavors of the American Baptist Missionary Union to South China in the Late Qing Dynasty - LI Qiyao, (Journal of Research for Christianity in China (JRCC), 2025)
This paper analyzes the archival materials of all six medical missionaries from the Southern China Mission of the American Baptist Missionary Union during the late Qing period. By presenting the fundamental circumstances of the mission's medical work in South China, it further explores the relationship between medical missionary work and direct evangelism, as well as its cross-gender dimensions. The aim is to gain a deeper understanding of church-sponsored medical initiatives in modern China.
Keywords: Medical Missionary, American Baptist Missionary Union, South China